Toponimy w nazwach roślin polikonfrontatywnie = Toponyms in Botanical names. A Polyconfrontative Approach - Urniaż, Agnieszka Jolanta (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In the article the author concentrates on polyconfrontative analysis of botanical names containing a toponym in their structure. The results of polyconfrontative research of the Latin binomial names with their equivalents in Polish, Czech, Dutch and English have been presented taking into consideration the degree of equivalence of the toponym in the species name.
Keywords: toponimy; nazewnictwo binominalne; epitet gatunkowy; badania porównawcze; toponyms; binomial nomenclature; specific epithet; polyconfrontative study